Study of Diabetes and Extrapulmonary Tuberculosis (Cervical Lymphoadenopathy, Skin TB, CNS TB, Plueural Tubercular Effusion) - Praveen K. Tagore; Prashant Harit; Mahendra K. Bharti; Manish K. Sachan; Gauri Harit; Pratima Singh (Journal of Pharmacy and Bioallied Sciences)
Background: Diabetes mellitus (DM) is a significant risk factor for tuberculosis (TB), increasing susceptibility to both pulmonary and extrapulmonary TB (EPTB). Extrapulmonary manifestations, including cervical lymphadenopathy, cutaneous tuberculosis (TB), central nervous system (CNS) TB, and pleural tubercular effusion, pose diagnostic and therapeutic challenges. Materials and Methods: A hospital-based observational study was conducted on 150 diabetic patients diagnosed with EPTB. The study population was divided into four groups based on the site of infection: cervical lymphadenopathy (n = 50), cutaneous TB (n = 40), CNS TB (n = 30), and pleural tubercular effusion (n = 30). Diagnosis was confirmed using histopathology, GeneXpert, culture, and imaging modalities. Glycemic control was assessed using HbA1c levels, and treatment outcomes were monitored over six months. Results: Among the study population, 65% were male, and 35% were female, with a mean age of 52.4 ± 8.7 years. Poor glycemic control (HbA1c >8.0%) was observed in 60% of the patients. The most prevalent manifestation was cervical lymphadenopathy (33.3%), followed by cutaneous TB (26.7%), CNS TB (20%), and pleural tubercular effusion (20%)**. Treatment success was noted in 78% of cases, while 15% showed partial response, and 7% had poor outcomes. Diabetic patients with poor glycemic control had significantly higher treatment failure rates (P < 0.05). Conclusion: Diabetes increases the risk of extrapulmonary TB, with cervical lymphadenopathy being the most common presentation. Poor glycemic control adversely affects treatment outcomes. Early diagnosis and strict glycemic management are essential for improving prognosis in diabetic patients with EPTB.